2014
DOI: 10.4314/wsa.v40i2.21
|View full text |Cite
|
Sign up to set email alerts
|

The Belmont Valley integrated algae pond system in retrospect

Abstract: Integrated Algae Pond Systems (IAPS) are a derivation of the Oswald-designed Algal Integrated Wastewater Pond Systems (AIWPS®) and combine the use of anaerobic and aerobic bioprocesses to effect sewage treatment. IAPS technology was introduced to South Africa in 1996 and a pilot plant designed and commissioned at the Belmont Valley WWTW in Grahamstown. The system has been in continual use since implementation, and affords secondarily treated water for reclamation according to its design specifications, which m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 76 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…Advanced Integrated Wastewater Pond System (AIWPS) or Integrated Algae Pond Systems (IAPS) integrate HRAPs with anaerobic and aerobic biological processes for wastewater treatment. Wastewater initially enters a covered anaerobic pond or advanced facultative pond where organic solids settle and decompose anaerobically producing biogas that is collected by a pond-cover for use as fuel [56,79,86]. Water laden with nutrients then flows to HRAPs where microalgae grow.…”
Section: Microalgal Wastewater Treatment For Biogas Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Advanced Integrated Wastewater Pond System (AIWPS) or Integrated Algae Pond Systems (IAPS) integrate HRAPs with anaerobic and aerobic biological processes for wastewater treatment. Wastewater initially enters a covered anaerobic pond or advanced facultative pond where organic solids settle and decompose anaerobically producing biogas that is collected by a pond-cover for use as fuel [56,79,86]. Water laden with nutrients then flows to HRAPs where microalgae grow.…”
Section: Microalgal Wastewater Treatment For Biogas Productionmentioning
confidence: 99%
“…The construction capital costs for an Advanced Pond System are <50%, and operational costs are <20% relative to activated sludge systems but require~50-fold the land area of activated sludge systems for the same Biological Oxygen Demand (BOD) removal, excluding the land area needed to dispose of waste activated sludge [56]. Where land constraints permit AIWPS and IAPS are now utilised globally for the remediation of wastewater [68,79,86,[88][89][90].…”
Section: Microalgal Wastewater Treatment For Biogas Productionmentioning
confidence: 99%
“…pH and Electrical conductivity (EC) were measured using a pH meter and conductimeter (HANNA) respectively. [32]. The microalgae sludge systems were set up using an approach similar to that of [36].…”
Section: Characteristics Of the Sludge Used In Bioreactorsmentioning
confidence: 99%
“…Preliminary results of this collaboration indicated that the sewage sludge from the wastewater treatment plant Grahamstown is not stabilised enough for reuse ,while, the sewage sludge from the wastewater treatment plant in Tiaret, Algeria is stabilised enough to allow for reuse [31]. The algal pond system is present here and has been studied extensively [32] Diatoms, e. Chlorella, f.Closterium, g.Chlamydomonas, h.Pyrobotrys,i. Euglena, j.Actinastrum,k.Dictyosphaerium, l. Blue greens.…”
Section: Introductionmentioning
confidence: 99%
“…A few of the recent reviews advocate for mixotrophic cultivation as a means to enhance biomass productivity [52,53,70,71], while the two-stage cultivation, with a luxury consumption stage followed by nitrogen limitation, is recommended for lipid production [58,70,71]. Both nutrient removal [72][73][74][75] and nutrient uptake [32,76,77] are discussed in the context of lipid production.…”
Section: Review Of Reviewsmentioning
confidence: 99%